Long-term changes in corneal structure and tear inflammatory mediators after orthokeratology and LASIK - González-Pérez, Javier (2012)
PURPOSE: To monitor changes in corneal structure and level of inflammatory mediators in tears of myopic patients following orthokeratology (OK) and laser in situ keratomileusis (LASIK). METHODS: Sixty-two myopic subjects were analyzed in this prospective study. Thirty-two had worn Paragon CRT contact lenses and 30 underwent standard LASIK. Thirty-two control subjects were also recruited. Pachometry and corneal topography were performed 12 months after both interventions. Tears were collected and assayed using ELISA for IL-6, IL-8, matrix metalloproteinase-9 (MMP-9), and epidermal growth factor (EGF). RESULTS: Corneal power decreased in the central area and increased in the paracentral area. Simultaneously, there was a central corneal thinning with mid-peripheral thickening for OK. No changes were observed for LASIK. In comparison with controls, IL-6, IL-8, MMP-9, and EGF levels were increased significantly for OK (P < 0.01). Only MMP-9 (P < 0.01) and EGF (P < 0.01) were increased for LASIK. Pro-inflammatory response was found to be associated with the degree of myopia in the OK group. The MMP-9 and EGF upregulation was linked to the presence of iron deposition in both groups, whereas increased levels of EGF were connected with the presence of myopic regression after LASIK. CONCLUSIONS: Both interventions involved important tissue reshaping. The physical presence of a reverse geometry contact lens caused certain markers to change significantly in comparison with no lens wear or LASIK in the long-term response. MMP-9 was significantly higher in tears of subjects presenting iron deposition after OK or LASIK, and EGF levels seemed to play an important role in postoperative refractive outcomes after LASIK.